Sex and Gender Differences in Stroke and Their Practical Implications in Acute Care - Johanna Ospel; Nishita Singh; Aravind Ganesh; Mayank Goyal (Journal of Stroke, 2023)
There are several controversies regarding the role of sex and gender in the pathophysiology and management of acute stroke. Assessing the role of sex, i.e., biological/pathophysiological factors, and gender, i.e., sociocultural factors, in isolation is often not possible since they are closely intertwined with each other. To complicate matters even more, the functional baseline status of women and men at the time of their first stroke is substantially different, whereby women have, on average, a poorer reported/ascertained baseline function compared to men. These differences in baseline variables account for a large part of the differences in post-stroke outcomes between women and men. Adjusting for these baseline differences is difficult, and in many cases, residual confounding cannot be excluded. Despite these obstacles, a better understanding of how patient sex and gender differences influence acute stroke and stroke care pathways is crucial to avoid biases and allow us to provide the best possible care for all acute stroke patients. Disregarding patient sex and gender on one hand and ignoring potential confounding factors in sex- and gender-stratified analyses on the other hand, may cause researchers to come to erroneous conclusions and physicians to provide suboptimal care. This review outlines sex- and gender-related factors in key aspects of acute stroke, including acute stroke epidemiology, diagnosis, access to care, treatment outcomes, and post-acute care. We also attempt to outline knowledge gaps, which deserve to be studied in further detail, and practical implications for physicians treating acute stroke patients in their daily practice.